Mass spectrometry detection of G3m and IGHG3 alleles and follow-up of differential mother and neonate IgG3 - Dechavanne, Célia; Guillonneau, François; Chiappetta, Giovanni; Sago, Laïla; Lévy, Prisca; Salnot, Virginie; Guitard, Evelyne; Ehrenmann, François; Broussard, Cédric; Chafey, Philippe; Le Port, Agnès; Vinh, Joëlle; et al. (Public Library of Science, 2012)
Mass spectrometry (MS) analysis for detection of immunoglobulins (IG) of the human IgG3 subclass is described that relies on polymorphic amino acids of the heavy gamma3 chains. IgG3 is the most polymorphic human IgG subclass with thirteen G3m allotypes located on the constant CH2 and CH3 domains of the gamma3 chain, the combination of which leads to six major G3m alleles. Amino acid changes resulting of extensive sequencing previously led to the definition of 19 IGHG3 alleles that have been correlated to the G3m alleles. As a proof of concept, MS proteotypic peptides were defined which encompass discriminatory amino acids for the identification of the G3m and IGHG3 alleles. Plasma samples originating from ten individuals either homozygous or heterozygous for different G3m alleles, and including one mother and her baby (drawn sequentially from birth to 9 months of age), were analyzed. Total IgG3 were purified using affinity chromatography and then digested by a combination of AspN and trypsin proteases, and peptides of interest were detected by mass spectrometry. The sensitivity of the method was assessed by mixing variable amounts of two plasma samples bearing distinct G3m allotypes. A label-free approach using the high-performance liquid chromatography (HPLC) retention time of peptides and their MS mass analyzer peak intensity gave semi-quantitative information. Quantification was realized by selected reaction monitoring (SRM) using synthetic peptides as internal standards. The possibility offered by this new methodology to detect and quantify neo-synthesized IgG in newborns will improve knowledge on the first acquisition of antibodies in infants and constitutes a promising diagnostic tool for vertically-transmitted diseases.